2022
DOI: 10.1038/s41598-022-15257-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified atmosphere packaging on the postharvest quality of mulberry leaf vegetable

Abstract: Fresh mulberry leaf vegetable is nutritive and becoming popular. However, available preservation technologies are deficient. In present work, the effects of two kinds of modified atmosphere packaging on postharvest quality of fresh mulberry leaf vegetable stored at 4 °C were evaluated. The respiration rate of samples in the modified polyethylene packages (MP20) was 12.88–22.65% lower than that in normal polyethylene packaging (CK). The content of total soluble solids, soluble protein, and total polyphenol in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The atmospheric concentrations of O 2 and CO 2 in the package depend largely on the permeability of the packaging bags during storage. The effects of PMAP on the quality changes of different horticultural crops have been widely evaluated, such as Chinese flowering cabbage, mulberry leaves, and pea pods after harvest ( Wang et al., 2020a ; Yang et al., 2022 ; Mou et al., 2023 , Mou et al, 2023 ; Luo et al., 2024 ). All the reported examples indicated that PMAP could efficiently regulated the gas concentrations inside of the packages, which might be induce series of physiological, biochemical, and molecular level regulations to delay the senescence process ( Wang et al., 2020b ; Mou et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The atmospheric concentrations of O 2 and CO 2 in the package depend largely on the permeability of the packaging bags during storage. The effects of PMAP on the quality changes of different horticultural crops have been widely evaluated, such as Chinese flowering cabbage, mulberry leaves, and pea pods after harvest ( Wang et al., 2020a ; Yang et al., 2022 ; Mou et al., 2023 , Mou et al, 2023 ; Luo et al., 2024 ). All the reported examples indicated that PMAP could efficiently regulated the gas concentrations inside of the packages, which might be induce series of physiological, biochemical, and molecular level regulations to delay the senescence process ( Wang et al., 2020b ; Mou et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The overall visual changes of sweet bamboo shoot (P. elegans) after passive modified atmosphere packaging (MP40) treatments during storage. The quality changes could be efficiently maintained by physical treatments with PMAP in both fruits and vegetables, such as Chinese flowering cabbage (Mou et al, 2023), bell pepper (Frans et al, 2021), and mulberry leaf vegetables (Yang et al, 2022). The treatment of PMAP was shown to modify the headspace gas concentration to further regulate oxidation and a series of physiological and biochemical senescence changes in the samples (Qu et al, 2022).…”
Section: B C Amentioning
confidence: 99%
“…With increasing storage time, two types of snow pea underwent enhanced lignin accumulation, and small snow peas were more susceptible to lignification than large sweet broad peas [40]. Lignin accumulation in samples in both modified polyethylene packages and normal polyethylene packaging gradually increased during storage [41]. Over the period of storage, enhanced respiration may require a significant amount of energy consumption, leading to accelerated senescence and the generation of reactive oxygen species, as well as the strengthened lignification process of horticultural products.…”
Section: Postharvest Storagementioning
confidence: 99%